Riyadhah Hifdzul Lisan Perspektif Imam Al Ghazali Dalam Kitab Ihya Ulumuddin - Yauma Fajariyanti Meliniar; Idrus Alkaf; Ahmad Soleh Sakni (CV. ITTC INDONESIA, 2024)
The tongue is one of the most influential tools in shaping a person's educational values, be it tawhid, or morals, because the good and bad of humans depends on how to be able to protect themselves from hurting others through the tongue, because today there are still many people who underestimate the dangers of the tongue itself such as gossiping, mocking here and there so that there is a dispute due to an unguarded tongue. Thus the above problems can be prevented by practicing riyadhah in maintaining the tongue according to Imam Al Ghazali's perspective. The purpose of this study is to find out how important the benefits of keeping the tongue. The method used in this research is qualitative research (Library Research) with Content Analysis research model. Data analysis used includes data reduction, data display and conclusion drawing / verification. The data collection technique in this study uses the documentation method which directs researchers in collecting record variables such as books, manuscripts and so on. Imam Al-Ghazali has explained four things that can be done by someone to do riyadhah in order to achieve self-purification (tazkiyah an-nafs) in fighting lust, namely; uzlah or khalwat (solitude), as-sukut or ash-shumt (silence), al-ju' (hunger), and as-sahr (waking up at night). The concept of riyadhah to keep the tongue according to Imam Al-Ghazali in the book Ihya Ulumuddin is by avoiding twenty oral dangers that have been explained in the book including: Useless speech, excessive speaking, speaking about falsehood, arguing and others.